Effects of CYP3A4*22 and CYP3A5 on clinical outcome in patients treated with ticagrelor for ST-segment elevation myocardial infarction: POPular Genetics sub-study - Azzahhafi, Jaouad; Bergmeijer, Thomas O.; van den Broek, Wout W. A.; Chan Pin Yin, Dean R. P. P.; Rayhi, Senna; Peper, Joyce; Bor, Willem L.; Claassens, Daniel M. F.; van Schaik, Ron H. N.; ten Berg, Jurriën M. (Frontiers in Pharmacology, 2022)
Aims: To determine the clinical efficacy, adverse events and side-effect dyspnea of CYP3A4*22 and CYP3A5 expressor status in ticagrelor treated patients. Methods and results: Ticagrelor treated patients from the POPular Genetics randomized controlled trial were genotyped for CYP3A4*22 and CYP3A5*3 alleles. Patients were divided based on their genotype. In total 1,281 patients with ST-segment elevation myocardial infarction (STEMI) were included. CYP3A4*22 carriers (n = 152) versus CYP3A4*22 non-carrier status (n = 1,129) were not found to have a significant correlation with the primary thrombotic endpoint: cardiovascular death, myocardial infarction, definite stent thrombosis and stroke [1.3% vs. 2.5%, adjusted hazard ratio 1.81 (0.43–7.62) p = 0.42], or the primary bleeding endpoint: PLATO major and minor bleeding [13.2% vs. 11.3%, adjusted hazard ratio 0.93 (0.58–1.50) p = 0.77]. Among the CYP3A4*1/*1 patients, CYP3A5 expressors (n = 196) versus non-expressors (n = 926) did not show a significant difference for the primary thrombotic [2.6% vs. 2.5%, adjusted hazard ratio 1.03 (0.39–2.71) p = 0.95], or the primary bleeding endpoint [12.8% vs. 10.9%, adjusted hazard ratio 1.13 (0.73–1.76) p = 0.58]. With respect to dyspnea, no significant difference was observed between CYP3A4*22 carriers versus CYP3A4*22 non-carriers [44.0% vs. 45.0%, odds ratio 1.04 (0.45–2.42) p = 0.93], or in the CYP3A4*1/*1 group, CYP3A5 expressors versus CYP3A5 non-expressors [35.3% vs. 47.8%, odds ratio 0.60 (0.27–1.30) p = 0.20]. Conclusion: In STEMI patients treated with ticagrelor, neither the CYP3A4*22 carriers, nor the CYP3A5 expressor status had a statistical significant effect on thrombotic and bleeding event rates nor on dyspnea. Clinical Trial Registration:ClinicalTrials.gov, identifier NCT01761786.